2021
DOI: 10.1007/s10796-021-10154-4
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating AI Adoption with Responsible AI Signals and Employee Engagement Mechanisms in Health Care

Abstract: Artificial Intelligence (AI) technology is transforming the healthcare sector. However, despite this, the associated ethical implications remain open to debate. This research investigates how signals of AI responsibility impact healthcare practitioners’ attitudes toward AI, satisfaction with AI, AI usage intentions, including the underlying mechanisms. Our research outlines autonomy, beneficence, explainability, justice, and non-maleficence as the five key signals of AI responsibility for healthcare practition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 103 publications
(158 reference statements)
1
22
0
Order By: Relevance
“…People tend to support technical changes (e.g., adopting new technology), but acceptance or rejection of the change will rely on their engagement levels [ 17 ]. High engagement is the key to successful technology adoption [ 17 , 65 ] and satisfaction [ 22 ]. Engaged patients are more likely to be involved in preventive behaviors, self-manage symptoms and treatments, affirmatively seek health information, become advisors to new patients, and promote peer support [ 66 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…People tend to support technical changes (e.g., adopting new technology), but acceptance or rejection of the change will rely on their engagement levels [ 17 ]. High engagement is the key to successful technology adoption [ 17 , 65 ] and satisfaction [ 22 ]. Engaged patients are more likely to be involved in preventive behaviors, self-manage symptoms and treatments, affirmatively seek health information, become advisors to new patients, and promote peer support [ 66 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Several researchers have reported that satisfaction positively influences patients’ continuous intentions [ 44 , 48 ], online and face-to-face consultation intention [ 68 ], usage intention [ 59 ], and m-health emergency use [ 25 ]. Satisfaction has also been found to positively affect AI [ 22 ]. However, travel expenses negatively affect AI [ 26 , 69 ], thus becoming the first encouragement of behavioral intentions in telemedicine [ 70 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the deployment of these technologies, there may also be an educative role for organizations in upskilling workers on the benefits and limitations of AI use. Managers, in particular, could benefit from training concerning the affordances of the technology, as well as an awareness of the dangers of perceiving AI as adding "extra workload" which has the potential to act as a "techno-stressor" which can influence AI justice perceptions and behavioral outcomes (Wang et al, 2021;cf. Yassaee and Mettler, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%